Serum-deprived differentiated neuroblastoma F-11 cells express functional dorsal root ganglion neuron properties - Valentina Pastori; Alessia D’Aloia; Stefania Blasa; Marzia Lecchi (PeerJ, 2019)
The isolation and culture of dorsal root ganglion (DRG) neurons cause adaptive changes in the expression and regulation of ion channels, with consequences on neuronal excitability. Considering that not all neurons survive the isolation and that DRG neurons are heterogeneous, it is difficult to find the cellular subtype of interest. For this reason, researchers opt for DRG-derived immortal cell lines to investigate endogenous properties. The F-11 cell line is a hybridoma of embryonic rat DRG neurons fused with the mouse neuroblastoma line N18TG2. In the proliferative condition, F-11 cells do not display a gene expression profile correspondent with specific subclasses of sensory neurons, but the most significant differences when compared with DRGs are the reduction of voltage-gated sodium, potassium and calcium channels, and the small amounts of TRPV1 transcripts. To investigate if functional properties of mature F-11 cells showed more similarities with those of isolated DRG neurons, we differentiated them by serum deprivation. Potassium and sodium currents significantly increased with differentiation, and biophysical properties of tetrodotoxin (TTX)-sensitive currents were similar to those characterized in small DRG neurons. The analysis of the voltage-dependence of calcium currents demonstrated the lack of low threshold activated components. The exclusive expression of high threshold activated Ca2+ currents and of TTX-sensitive Na+ currents correlated with the generation of a regular tonic electrical activity, which was recorded in the majority of the cells (80%) and was closely related to the activity of afferent TTX-sensitive A fibers of the proximal urethra and the bladder. Responses to capsaicin and substance P were also recorded in ~20% and ~80% of cells, respectively. The percentage of cells responsive to acetylcholine was consistent with the percentage referred for rat DRG primary neurons and cell electrical activity was modified by activation of non-NMDA receptors as for embryonic DRG neurons. These properties and the algesic profile (responses to pH5 and sensitivity to both ATP and capsaicin), proposed in literature to define a sub-classification of acutely dissociated rat DRG neurons, suggest that differentiated F-11 cells express receptors and ion channels that are also present in sensory neurons.